Supplement to value added tax: the British system explained - Joseph, Clifford (Berkshire Burchett's Green, 1972)
This is a supplement to the original white paper, and brings the book up-to-date to the 15th October 1972. It contains references to all the amendments made since the publication of the white paper, both in the Finance Bill and in the delegated legislation
osc 21/01/2019
Loans
Keywords: Value Added Tax; Britain